The welding of aluminium and its alloys - Mathers, Gene (CRC Press ; Woodhead Pub., 2002)
The welding of aluminium and its alloys is a practical user's guide to all aspects of welding aluminium and aluminium alloys, giving a basic understanding of the metallurgical principles involved. The book is intended to provide engineers with perhaps little prior acquaintance with the welding processes involved a concise and effective reference to the subject. It covers weldability of aluminium alloys; process descriptions, advantages, limitations, proposed weld parameters, health and safety issues; preparation for welding, quality assurance and quality control issues. It is essential reading for welding engineers, production engineers, production managers, designers and supervisors involved in the aluminium fabrication industry.
Keywords: Aluminum -- Welding.; elektronické knihy; electronic books